Study of shrinkage phenomenon during convective drying of papaya (Carica papaya L.). - EL-AOUAR, A. A. (2005)
The aim of this work was to study the mate rial dimensions and bulk density changes during the convective drying of papaya ( Carica papaya L. ) slices and to model the sh rinkage kinetics.